ANALISIS NILAI KEPEMIMPINAN FIQIH SIYASAH DALAM PRAKTIK POLITIK DINASTI DI INDONESIA - KURNIA FITRI ROMDHLONI (LPPM-IAI BATAM, 2025)
Abstract Bahasa Inggris Islamic sharia does not explicitly regulate dynastic political law. Some literature states that if the implementation meets the elements of leadership according to sharia, it is allowed. However, looking at the condition of democracy in Indonesia, the proliferation of dynastic politics seriously threatens the integrity of leadership. This phenomenon is interesting to study, especially related to the leadership value of fiqh siyasah. This research has also not been done much. This study aims to analyze the political leadership of dynasties in Indonesia based on the perspective of the leadership values of Fiqih Siyasah. The researcher used a descriptive qualitative approach with a literature study method. Data is obtained from primary and secondary sources. The results of the study indicate that dynastic politics are contrary to the principles of leadership in Fiqh Siyasah. Dynastic politics does not reflect leaders who are obedient to democracy and the applicable constitution, do not realize fair and transparent election of leaders, and the ease of gaining power has the opportunity to make leaders untrustworthy. Keywords: Dynastic Politics, Leadership Values, Fiqh Siyasah Abstrak Bahasa Indonesia Syariat islam tidak mengatur secara eksplist mengenai hukum politik dinasti. Beberapa literatur menyebutkan apabila pelaksanaanya memenuhi unsur kepemimpinan menurut syariat maka diperbolehkan. Namun, melihat kondisi demokrasi di Indonesia, menjamurnya politik dinasti sangat mengancam integritas kepemimpinan. Fenomena ini menarik untuk dikaji, khususnya berkaitan dengan nilai kepemimpinan fiqih siyasah. Penelitian ini juga belum banyak dilakukan. Penelitian ini bertujuan menganalisis kepemimpinan politik dinasti di Indonesia berdasarkan perspektif nilai kepemimpinan Fiqih Siyasah. Peneliti menggunakan pendekatan kualitatif deskriptif dengan metode studi pustaka. Data diperoleh dari sumber primer dan sekunder. Hasil penelitian mengindikasikan bahwa politik dinasti bertentangan dengan prinsip kepemimpinan dalam Fiqih Siyasah. Politik dinasti tidak mencerminkan pemimpin yang taat dan patuh pada demokrasi dan konstitusi yang berlaku, tidak mewujudkan pemilihan pemimpin yang adil dan transparans, dan kemudahan memperoleh kekuasaan berpeluang menjadikan pemimpin tidak amanah. Kata Kunci: Politik Dinasti, Nilai Kepemimpinan, Fiqih Siyasah